(untitled) (Bangladesh Journal of Medical Science, 2012)
Background: The degree of physical activity may induce strain and stress on the Achilles tendon because of its role in the elastic mechanics of gait. Material &Methods: The study was carried out to determine the effect of occupation-related physical activity on the thickness of the Achilles tendon. The effect of occupation- related physical activity on the thickness of the Achilles tendon in three phases (ATT at Normal phase, ATT at Dorsiflexed phase and ATT at Plantarflexed phase) was assessed, by ultrasound, among four classes of occupations- Labourers/farmers, Dancers, Athletes and a less active class (control group). Results: Results show that the less active (control group) had the least value for ATT (normal) (3.31±0.50mm) being almost at par with those of the dancers. The athletes and labourers/farmers had significantly higher values than the control (P=0.000 and 0.007 respectively). Conclusion: Our findings have conclusively established that occupation-related prolonged physical activity induces thickening of the Achilles tendon. DOI: http://dx.doi.org/10.3329/bjms.v11i2.9666 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 103-111